P1239 Better quality of life in BRCA mutation carriers after salpingectomy with delayed oophorectomy compared to salpingo-oophorectomy; first results of the Dutch TUBA study. (1st November 2019) - Steenbeek, MP; Harmsen, MG; Hoogerbrugge, N; Arts-de Jong, M; Maas, AHEM; Prins, JB; Bulten, J; Teerenstra, S; Piek, JMJ; van Doorn, HC; van Beurden, M; Mourits, MJE; et al.
Abstract : Introduction/Background: Risk-reducing salpingo-oophorectomy (RRSO) around the age of 40 is recommended for BRCA1/2 germline mutation carriers. As recent data indicate the Fallopian tube as origin of high grade serous ovarian carcinoma (HGSC), risk-reducing salpingectomy (RRS) with delayed oophorectomy (RRO) is studied as an innovative strategy to delay premature menopause. The TUBA-study (NCT02321228 ) compares menopause-related quality of life (QOL) between standard RRSO and the innovative RRS with delayed RRO. Methodology: A multicentre preference trial in 13 Dutch centres started in January 2015. BRCA1/2 mutation carriers choose between the standard strategy (RRSO at age 35–40 ( BRCA 1) or 40–45 ( BRCA 2)) and the innovative strategy (RRS with delayed RRO until the age of 40–45 ( BRCA 1) or 45–50 years ( BRCA 2)). Results: August first 2019, 493 participants were included with a mean age of 37 years: 51% carried a BRCA1 and 49% carried a BRCA2 mutation. In total, 72% of women chose RRS with delayed RRO. At three months and one year after surgery, data showed a better menopause-related QOL in women after RRS when compared to women after RRSO (P<0.001), also after adjustment for age, hospital and baseline score. Additionally, a decline in cancer worry was found at three months and one year after surgery in both groups. Conclusion: The menopause-related QOL is significantly better in BRCA mutation carriers after RRS (with delayed RRO) when compared to RRSO. Furthermore, a favourable effect on cancer worry is found among participating women in both arms. At the time of the conference we will have finished recruitment and have one year of follow up in more than 300 women. Based on our results, the Dutch TUBA and American WISP study (NCT02760849 ) are initializing a combined international TUBA-WISP-II study to assess the safety of RRS with delayed RRO in BRCA germline mutation carriers. Disclosure: Nothing to disclose.